2007
DOI: 10.1002/hpm.883
|View full text |Cite
|
Sign up to set email alerts
|

Financial profiling of public hospitals: an application by data mining

Abstract: SUMMARYThis paper presents an application of the data mining method to determine the financial profiles of the public hospitals in Turkey. The study is based on the data compiled in 2004, covering 645 public hospitals run by the Ministry of Health (MoH) as the main provider of primary and secondary health services in Turkey. The public hospitals, currently financed by a mixture of funds allocated from the general budget and individually operated revolving funds, need urgent solutions to their financial problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
5
0
3
Order By: Relevance
“…Autonomous hospitals are usually financed by a mixture of funding approaches (Ozgulbas and Koyuncugil, 2009). Since the 1995 reforms in Iran (Health Deputy of MOHME, 1995), civil servants personnel's salaries (excluding their overtime and benefits), development budgets, and some subsidizes for hospitals' social functions are paid by the government.…”
Section: Resultsmentioning
confidence: 99%
“…Autonomous hospitals are usually financed by a mixture of funding approaches (Ozgulbas and Koyuncugil, 2009). Since the 1995 reforms in Iran (Health Deputy of MOHME, 1995), civil servants personnel's salaries (excluding their overtime and benefits), development budgets, and some subsidizes for hospitals' social functions are paid by the government.…”
Section: Resultsmentioning
confidence: 99%
“…Koyuncugil and Ozgulbas [22] found that 62% of public hospitals performed as low and suggested benchmarking to solve this issue. To identify and clarifying the relationship between the variables and to find useful but undiscovered patterns in collected financial data, Koyuncugil and Ozgulbas used Data Mining in hospital [23] classified the hospitals by their financial profiles and identified the 90.85% of public hospitals had low financial performance. Indicators show that Turkish Health Services had issues in present, provide, finance and organize health services in line with effectiveness, productivity and equity.…”
Section: Introductionmentioning
confidence: 99%
“…Ressalta-se que um aspecto essencial da gestão hospitalar está relacionado à gestão financeira (GRUEN;HOWARTH, 2005). Diversos estudos veem destacando a importância da administração dessa área nos hospitais, com ênfase no emprego de indicadores financeiros, com a finalidade de analisar o desempenho destes (ZELLER et al, 1996;BITTAR, 2001;OZGULBAS;KOYUNCUGIL, 2009;VELOSO, MALIK, 2010).…”
Section: Introductionunclassified